Educational practices in prostitution: experiences in the Associação Sergipana de Prostitutas - Ian Ravih Rollemberg de Aragão; Ilka Miglio de Mesquita; Luzinete Rosa dos Santos (Tópicos Educacionais)
This article aims to discuss the presence of educational practices in prostitution from a decolonial perspective, based on the experiences of the Associação Sergipana de Prostitutas. In this sense, its central problem involves the following questions: How are the educational practices in prostitution configured? Is a dialogue between Education and the study of prostitution possible from a critical and decolonial perspective? To answer these questions, we conducted a literature review investigating what the literature in the field of Education indicates regarding prostitution. Then, we employed documental research with the marks of ASP experiences. As a theoretical referential we used Walsh's (2008) understandings of Decolonial Pedagogy. We found that the actions performed by the ASP are alternative pedagogies, capable of educating women in the practice of prostitution.